MA Defence: â€œShaping The Genohype: A Cautionary Tale of Overpromiseâ€ by Stephan Struve - Phan, Vu Thuy Anh (Stream: Interdisciplinary Journal of Communication, 2015)
Our dear colleague, Stephan Struve, will defend his MA thesis on Thursday, December 3rd, 2015 at Harbour Centre, Room 2200 (10:00 am -12:00 pm). Here is the abstract of his thesis “Shaping the Genohype: A Cautionary Tale of Overpromise”.